THE STRUCTURE OF MUSIC PRESENTATION IN BALIATN RITUAL OF DAYAK KANAYATN - Yudhistira Oscar Olendo (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2020)
Traditional music in baliatn ritual has a composition or structure of special music presentation which can influence pamaliatn or tukang liatn (the ritual leader) to experience the transcendental period. Besides, the music played can incur the magical power, it indicates how strong the effect of the sound or voice of gongs, dau, and gadobokng that were played during baliatn ritual. The research problem was how does the structure of music presentation in baliatn ritual of Dayak Kanayatn? Thus, the purpose of this research was to describe and analyze the problem in the structure of music presentation of baliatn ritual. The research used descriptive method in qualitative research design. The study has found that the structure of music presentation in baliatn ritual held in three steps; the beginning part is guntur mandayu beating motif, the main part is ka ‘bawakng beating motif, and the final part is ne’ unte beating motif. In this research, the researcher also made the notation of Dayak Kanayatn music in special and simple way.